Perinatal and childhood origins of cardiovascular disease - Huang, R.; Burke, V.; Newnham, J.; Stanley, F.; Kendall, Garth; Landau, L.; Oddy, Wendy; Blake, K.; Palmer, L.; Beilin, L. (Nature Publishing Group, 2007)
Background: Features of the metabolic syndrome comprise a major risk for cardiovascular disease and will increase in prevalence with rising childhood obesity. We sought to identify early life influences on development of obesity, hypertension and dyslipidemia in children.Methods and results: Cluster analysis was used on a subset of a longitudinal Australian birth cohort who had blood samples at age 8 (n=406). A quarter of these 8-year-olds fell into a cluster with higher body mass index, blood pressure (BP), more adverse lipid profile and a trend to higher serum glucose resembling adult metabolic syndrome. There was a U-shaped relationship between percentage of expected birth weight (PEBW) and likelihood of being in the high-risk cluster. The high-risk cluster had elevated BP and weight as early as 1 and 3 years old. Increased likelihood of the high-risk cluster group occurred with greatest weight gain from 1 to 8 years old (odds ratio (OR)=1.4, 95% confidence interval (CI)=1.3?1.5/kg) and if mothers smoked during pregnancy (OR=1.82, CI=1.05?3.2). Risk was lower if children were breast fed for 4 months (OR=0.6, 95% CI=0.37?0.97). Newborns in the upper two quintiles for PEBW born to mothers who smoked throughout pregnancy were at greatest risk (OR=14.0, 95% CI=3.8?51.1) compared to the nadir PEBW quintile of non-smokers.Conclusion: A U-shaped relationship between birth weight and several components of the metabolic syndrome was confirmed in a contemporary, well-nourished Western population of full-term newborns, but post-natal weight gain was the dominant factor associated with the high-risk cluster. There was a prominence of higher as well as lowest birth weights in those at risk. Future health programs should focus on both pre- and post-natal factors (reducing excess childhood weight gain and smoking during pregnancy), and possibly the greatest benefits may arise from targeting the heaviest, as well as lightest newborns, especially with a history of maternal smoking during pregnancy.